Dryocrassin ABBA, a novel active substance for use against amantadine-resistant H5N1 avian influenza virus - Ou, Changbo; Zhang, Qiang; Wang, Juan; Wu, Guojiang; Shi, Ningning; He, Cheng; Gao, Zengping (Frontiers in Microbiology, 2015)
The occurrence of multi-drug resistant highly pathogenic avian influenza virus (HPAIV) strains highlights the urgent need for strategies for the prevention and control of avian influenza virus. The aim of our current study is to evaluate the antiviral activity of dryocrassin ABBA isolated from Rhizoma Dryopteridis Crassirhizomatis (RDC) against an amantadine-resistant H5N1 (A/Chicken/Hebei/706/2005) strain in a mouse model. Post inoculation with HPAIV H5N1 virus in mice, the survival rate was 87%, 80% and 60% respectively in the 33mg/kg, 18mg/kg and 12.5 mg/kg Dryocrassin ABBA-treated groups. On the other hand, the survival rate was 53% and 20%, respectively in the amantadine-treated group and untreated group. Mice administered dryocrassin ABBA or amantadine showed a significant weight increase compared to the untreated group. Moreover, 33 mg/kg and 18 mg/kg dryocrassin ABBA have decreased lung index (P>0.05) and virus loads (P<0.01) compared to the untreated group on day 7. Also, on day 7 bronchoalveolar lavage fluid pro-inflammatory cytokines (IL-6, TNF-α and IFN-γ) decreased significantly (P<0.01) while anti-inflammatory cytokines (IL-10 and MCP-1) were increased significantly (P<0.01) in the 33 mg/kg and 18 mg/kg dryocrassin ABBA-treated groups compared to the amantadine group and the untreated group. Moreover, the concentrations of IL-12 in drug-treated groups were significantly (P<0.01) lowered compared with the untreated group. Based on the above we conclude that orally administered dryocrassin ABBA provided mice protection against avian influenza virus H5N1 by inhibiting inflammation and reducing virus loads. Dryocrassin ABBA is a potential novel lead compound which had antiviral effects on amantadine-resistant avian influenza virus H5N1 infection.